Estudio experimental comparativo de resistencias entre pavimentos rígidos y pavimentos con fibras plásticas, como alternativa para la rehabilitación de las ciclovías de Bogotá. (2021)
Colombia is a country that invests a lot of capital in the development of its road infrastructure, however, there are currently marked differences between the different types of road infrastructure, for example, according to the latest inventory and diagnosis of the road network conducted by the IDU, there are 14,186 km of roads in Bogota, while there are only just over 550 km of bicycle lanes, a notable disadvantage, considering that an increasing number of the capital's inhabitants make daily trips by bicycle, not to mention the state of the infrastructure.